ANALISA PEMASANGAN KAPASITOR UNTUK MENINGKATKAN FAKTOR DAYA PADA TRAFO1 DI HOTEL MELIA BALI - I Kadek Satrya Anggara Putra; I Made Suartika; I Wayan Rinas (Jurnal SPEKTRUM, 2020)
Melia Bali-Indonesia Hotel is the first hotel of Sol Melia's management, which subsequently becomes the Bali Sol Hotel. This hotel was supplied from transformer 1 of the Melia Bali Hotel via MDP1 with 9 SDPs, with priority to supply electricity to rooms and villas. Based on the measurement results obtained currents: at each phase namely: phase R = 456 A, phase S = 445 A, phase T = 412 A and power factor of 0,84. A power factor of less than 0,85, based on the determination of an electric power tariff adjustment from PT PLN, may be subject to excess reactive power usage fees (Regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia Number 28 of 2016). Based on these data, an analysis of the installation of capacitors was carried out to increase the power factor in transformer 1 of Melia Bali Sol. The method used is to use simulation modeling with ETAP. Based on the results of the analysis of the installation of capacitors can increase the power factor by 11% to 0,95, already exceeding the minimum average power factor determined by the PLN electricity tariff adjustment. In addition, the load current decreased 12% from 442.3 A to 389.5 A.